Introduction to Instrumentation - Northrop, Robert B. (CRC Press, Taylor & Francis Group, 2014)
Weighing in on the growth of innovative technologies, the adoption of new standards, and the lack of educational development as it relates to current and emerging applications, the third edition of Introduction to Instrumentation and Measurements uses the authors' 40 years of teaching experience to expound on the theory, science, and art of modern instrumentation and measurements (I&M). This edition includes material on modern integrated circuit (IC) and photonic sensors, micro-electro-mechanical (MEM) and nano-electro-mechanical (NEM) sensors, chemical and radiation sensors, signal conditioning, noise, data interfaces, and basic digital signal processing (DSP), and upgrades every chapter with the latest advancements. It contains new material on the designs of micro-electro-mechanical (MEMS) sensors, adds two new chapters on wireless instrumentation and microsensors, and incorporates extensive biomedical examples and problems.